The Influence of Career Development, Training and Competence On Employee Performance In Indonesian Telecommunications Companies - Zackia Putri Widiyanti; Ayu Nadilah; Lisa Harry Sulistiyowati (International Journal of Business, Economics, and Social Development, 2025)
This study aims to analyze the influence of career development, training, and competence on employee performance at the Indonesian Digital Telecommunications company. The method used in this study is an associative quantitative approach with data collection through questionnaires distributed to employees of the Indonesian Digital Telecommunications company. The population in this study were 172 permanent employees at a telecommunications company in Cirebon. The sample in this study was 120 respondents. Data processing in this study used the SPSS 25.0 For Windows program. Multiple linear regression analysis was employed to assess the relationship between the independen and dependent variables. The study’s results show that career development has a positive and significant effect on employee performance, and training likewise exhibits a positive and significant influence on employee performance, and Competence has a significant effect on employee performance